2023
DOI: 10.1590/0103-6440202305278
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of Bioactive Endodontic Materials

Abstract: A continuous search for bioactive materials capable of supporting the replacement of damaged pulp tissue, with effective sealing potential and biocompatibility, has represented the attention of studies over the last decades. This study involves a narrative review of the literature developed by searching representative research in PUBMED/MEDLINE and searches in textbooks associated with the mechanism of action of bioactive materials (calcium hydroxide, mineral trioxide aggregate (MTA), and calcium silicate ceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 83 publications
(141 reference statements)
1
8
0
2
Order By: Relevance
“…[ 19 ] Raising the pH level can cause damage to the cytoplasmic membrane, DNA, and proteins, which can lead to the death of bacteria as well as the host cells. [ 20 ] Results of the current study are consistent with Loushine et al . who found that at the 24-h period, the cytotoxicity of Endosequence BC sealer was greater compared to AH Plus and justified that by the more extended final setting time of the bioceramic sealer that could lead to the components leaching over a prolonged period and negatively influence cell viability.…”
Section: Discussionsupporting
confidence: 93%
“…[ 19 ] Raising the pH level can cause damage to the cytoplasmic membrane, DNA, and proteins, which can lead to the death of bacteria as well as the host cells. [ 20 ] Results of the current study are consistent with Loushine et al . who found that at the 24-h period, the cytotoxicity of Endosequence BC sealer was greater compared to AH Plus and justified that by the more extended final setting time of the bioceramic sealer that could lead to the components leaching over a prolonged period and negatively influence cell viability.…”
Section: Discussionsupporting
confidence: 93%
“…Heating did not alter the alkalinity of all the tested sealers which corroborates with previous publications 3 , 4 , 6 . The high pH values of the tricalcium silicate sealers are related to the formation of Portlandite (calcium hydroxide) as a hydration product, which results in calcium and hydroxyl ions released 6 , 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The cavity volume (Vc) and the root-end filling material volume (Vm) were measured in mm 3 . Then the following parameters were calculated: (1) the volume of the interfacial gaps and voids present in the material-to-dentin wall interface, defined as open porosity volume for brevity (OPV); and (2) the volume of micropores within the material, defined as closed porosity volume (CPV).…”
Section: Micro-ct Scans and Analysismentioning
confidence: 99%
“…The quantities of both the internal and interfacial porosity fractions were measured separately and as the total amount (TPV). They were calculated as absolute values in mm 3 and relative values in percentages.…”
Section: Micro-ct Scans and Analysismentioning
confidence: 99%
See 1 more Smart Citation